2020
DOI: 10.3390/cancers12061402
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer Staging: Is It Time for Magnetic Resonance Imaging?

Abstract: Gastric cancer (GC) is a common cancer worldwide. Its incidence and mortality vary depending on geographic area, with the highest rates in Asian countries, particularly in China, Japan, and South Korea. Accurate imaging staging has become crucial for the application of various treatment strategies, especially for curative treatments in early stages. Unfortunately, most GCs are still diagnosed at an advanced stage, with the peritoneum (61–80%), distant lymph nodes (44–50%), and liver (26–38%) as the most common… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Among the biological mechanisms involved in anticancer immunity, T-cell adaptive immunity has been suggested to play a key role in this setting [ 56 ]; more specifically, CD8+ T cells, CD4+ T helper cells, FOXP3+ regulatory T cells, memory T cells, and NK cells can infiltrate the stromal tissue, thus modifying the host immune response against cancer cells [ 57 , 58 ]. Over the last decade, several reports have highlighted that the GC microenvironment could be associated with the infiltration of tumor lymphocytes [ 5 , 59 ]. TILs may cause potent anticancer responses, preventing tumor growth and eradicating cancer cells; moreover, TILs have been suggested to enhance inflammation through the secretion of chemokines, cytokines, and matrix metalloproteinases [ 60 , 61 ].…”
Section: Lymphocytesmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the biological mechanisms involved in anticancer immunity, T-cell adaptive immunity has been suggested to play a key role in this setting [ 56 ]; more specifically, CD8+ T cells, CD4+ T helper cells, FOXP3+ regulatory T cells, memory T cells, and NK cells can infiltrate the stromal tissue, thus modifying the host immune response against cancer cells [ 57 , 58 ]. Over the last decade, several reports have highlighted that the GC microenvironment could be associated with the infiltration of tumor lymphocytes [ 5 , 59 ]. TILs may cause potent anticancer responses, preventing tumor growth and eradicating cancer cells; moreover, TILs have been suggested to enhance inflammation through the secretion of chemokines, cytokines, and matrix metalloproteinases [ 60 , 61 ].…”
Section: Lymphocytesmentioning
confidence: 99%
“…tissue, thus modifying the host immune response against cancer cells [57,58]. Over the last decade, several reports have highlighted that the GC microenvironment could be associated with the infiltration of tumor lymphocytes [5,59]. TILs may cause potent anticancer responses, preventing tumor growth and eradicating cancer cells; moreover, TILs have been suggested to enhance inflammation through the secretion of chemokines, cytokines, and matrix metalloproteinases [60,61].…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuous technical improvements have shown that it can enhance high contrast resolution and characteristic soft-tissue of magnetic resonance imaging (MRI), especially the diagnostic value of small liver metastases (≤10mm) and peritoneal implantation (29)(30)(31). However, MRI is usually associated with higher costs, longer acquisition time and a lower robustness with no major oncology guidelines to recommend preoperative evaluation of GC (32)(33)(34)(35). In contrast, the predictive value of 18F FDG PET/CT was high in several metastasis from GC including peritoneal metastasis, however, its limited usability and high costs would only make PET an alternative imaging modality 36).…”
Section: Discussionmentioning
confidence: 99%
“…Sophisticated CT and magnetic resonance imaging or sentinel node mapping techniques[ 137 138 ] are being developed to high-resolution capacities at least as potent as the old conventional EUS. [ 139 140 ] However, none of them can capture micrometastases <5 mm. [ 141 ]…”
Section: Is There a Role For Eus Miniprobes In N-staging In Early Gastric Cancers?mentioning
confidence: 99%